Embedding a serious game into an ESP curriculum - Pappa, Giouli; Papadima-Sophocleous, Salomi (My University, 2019)
This paper describes how a selected Commercial Off-The-Shelf (COTS) Serious Game (SG) was evaluated before being integrated into an English for Specific Purposes (ESP) curriculum. Echoing the concerns of language practitioners regarding the adoption of SGs into their teaching practices, this paper describes the steps and decisions taken before the selected COTS SG implementation into a specific learning context; that of the course English for shipping at the Cyprus University of Technology (CUT). A combination of methods was initiated towards assessing the COTS SG. It was carried out following the qualitative embedded single case study research design, as this research explores only one case; that of the assessment of the SG called Escape From Desolo. The aim of the case study was to explore the areas of ESP teaching with COTS SGs by illustrating a combination of assessment methods that could be adopted by those considering SG embedding in formal ESP language settings. The present chapter first outlines the reasons which initiated such integration. The initial assessment of the selected SG and the game design, which is carried out with the use of the Relevance, Embedding, Transfer, Adaptation, Immersion, and Naturalisation (RETAIN) model, is discussed. This is followed by further evaluation of the particular SG, which occurred with the use of the four-dimensional framework. After evaluating its pedagogical use, an analysis of the application of the selected tool within the curriculum is presented. Both the model and the framework are presented in detail in the chapter. Although this study focusses on English for shipping, it is hoped that this process may be applied in different ESP contexts for future studies. The results of the evaluation of the chosen SG with the use of the model and the framework indicated their usefulness in assessing a SG intended to be used in an ESP teaching and learning context. It is hoped that this case can prove beneficial in other ESP learning contexts. [For the complete volume, "ESP Teaching and Teacher Education: Current Theories and Practices," see ED595614.]
Keywords: Formal education; Serious games; COTS; Escape From Desolo; RETAIN; Four-dimensional framework